The process of developing professional capacity for teachers - Ho, Van-Thong; Tran, Van-Dat; Nguyen, Van-De; Phan, Trong-Nam; Cao, Thanh-Hung (Journal of Education and e-Learning Research, 2023)
The primary aim of Vietnam’s new educational program is to enhance students’ knowledge and skills through practical learning experiences, enabling them to tackle academic and real-world challenges. However, teachers in Dong Thap province face limitations in their professional competencies. Thus, this study aims to address these issues by examining different models for developing teachers’ professional competencies. 1,116 participants participated in this study (258 managers and 868 teachers from high schools and preschools) who completed two questionnaires assessing their professional competence and the perceived importance of professional development. The findings reveal that teachers lack subject knowledge, interdisciplinary understanding and skills in teaching design and assessment. Both school managers and teachers recognize the necessity of professional competence development. A three-step process for enhancing teachers’ professional competence is proposed for implementing professional development activities based on these findings.